Factors influencing the extent of deployment of electronic commerce for small and medium-sized enterprises - Chong, Sandy; Pervan, Graham (IGI Global, 2007)
This study surveys the perceptions and experiences of Australian small- and medium-sized enterprises (SMEs) in the implementation of Internet-based Electronic Commerce (EC) as seen from the perspective of the extent of deployment. With a sample of 115 small businesses in Australia, this article uses regression modelling to explore and establish the factors that are related to the extent of deployment in EC. A multiple regression analysis shows that seven factors: perceived relative advantage, trialability, observability, variety of information sources, communication amount, competitive pressure, and non-trading institutional influences, significantly influence the extent of EC deployment by SMEs in Australia. The managerial implications are discussed.